2020
DOI: 10.1016/j.gie.2020.03.2132
|View full text |Cite
|
Sign up to set email alerts
|

Su1286 ENDOSCOPIC ULTRASOUND-GUIDED GASTROJEJUNOSTOMY IS SUPERIOR TO DUODENAL SELF EXPANDABLE METAL STENT FOR PALLITAIVE TREATMENT OF MALIGNANT GASTRIC OUTLET OBSTRUCTTION: A COMPARATIVE CASE CONTROL STUDY

Abstract: Background: Palliative treatment of malignant gastric outlet obstruction (GOO) is typically obtained by endoscopic placement of a duodenal self expandable metal stent (D-SEMS), with excellent results in the short-term, but with a high incidence of D-SEMS disfunction due to tumor overgrowth in the long-term. Whether endoscopic ultrasound-guided gastrojejunostomy (EUS-GJ) may be a better alternative for this type of patients remains to be proved. Aim: To compare the performance characteristics of EUS-GJ and D-SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…We were unable to analyze if one EUS-GE technique was superior to the other. In our analysis, only three studies reported on the location of obstruction 43 46 47 . This was duodenal bulb in 130 patients, second portion of duodenum in 190 patients and distal duodenum in 129 patients.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…We were unable to analyze if one EUS-GE technique was superior to the other. In our analysis, only three studies reported on the location of obstruction 43 46 47 . This was duodenal bulb in 130 patients, second portion of duodenum in 190 patients and distal duodenum in 129 patients.…”
Section: Discussionmentioning
confidence: 93%
“…A total of five studies, with 659 patients were included in the final analysis 43 44 45 46 47 . A schematic diagram demonstrating our study selection is illustrated in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of seven studies involving 625 patients were included in the final analysis 22 23 24 25 26 27 40 . Single-arm studies on EUS-GE 12 17 18 41 42 43 44 , and/or comparing EUS-GE to only endoscopic stenting 19 45 46 47 were excluded. A schematic diagram demonstrating our study selection is illustrated in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%